2021
DOI: 10.1186/s13068-021-02087-6
|View full text |Cite
|
Sign up to set email alerts
|

Improved methanol tolerance of Rhizomucor miehei lipase based on N‑glycosylation within the α-helix region and its application in biodiesel production

Abstract: Background Liquid lipases are widely used to convert oil into biodiesel. Methanol-resistant lipases with high catalytic activity are the first choice for practical production. Rhizomucor miehei lipase (RML) is a single-chain α/β-type protein that is widely used in biodiesel preparation. Improving the catalytic activity and methanol tolerance of RML is necessary to realise the industrial production of biodiesel. Results In this study, a semi-rationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Although the methanol tolerance of both ROL mutants is lower than that of Eversa (80% v / v ), we see a strong correlation between the thermostability and methanol tolerance of the ROL mutants. Such correlation has been observed in many other enzymes including lipases [ 23 , 24 , 25 , 26 , 27 ]. This finding suggests that further improvement to the thermostability of ROL might increase their tolerance towards organic solvent, which have the potential to be used for biodiesel production.…”
Section: Resultssupporting
confidence: 60%
“…Although the methanol tolerance of both ROL mutants is lower than that of Eversa (80% v / v ), we see a strong correlation between the thermostability and methanol tolerance of the ROL mutants. Such correlation has been observed in many other enzymes including lipases [ 23 , 24 , 25 , 26 , 27 ]. This finding suggests that further improvement to the thermostability of ROL might increase their tolerance towards organic solvent, which have the potential to be used for biodiesel production.…”
Section: Resultssupporting
confidence: 60%
“…Using the commercial lipase Novozyme ® 435, edible waste oil was used as raw material to produce biodiesel via enzymecatalyzed regeneration (Sorte et al, 2020). Moreover, M. Tian et al (2021) proved that Rhizomucor miehei lipase, which is a single-chain α/β-type protein, was found to be widely used in biodiesel production due to its catalytic activity and methanol tolerance. One year later, the same authors have used a semirational directed evolution method combined with N-glycosylation to enhance catalytic activity and methanol tolerance (M. Tian et al, 2022).…”
Section: Fungal Lipases In Biodiesel Productionmentioning
confidence: 99%
“…In such cases, recombinant forms are favored to conquer the demand of purification protocols (Lotti & Alberghina, 2007). For example, some new results have shown that N-glycosylation modification in the α-helix structure of Rhizomucor miehei lipase proved to be an effective strategy for improving the performance of this lipolytic enzyme in biodiesel applications (M. Tian et al, 2021).…”
Section: Other Sectorsmentioning
confidence: 99%
“…The heightened awareness of actively mitigating climate change, reducing pollution, and improving food security has driven the need for biomanufacturing. Biosynthesis provides a key platform for bioproduction [ 1 ], including green synthesis of biodiesel [ 2 , 3 , 4 ], ethanol [ 5 , 6 ], organic acids [ 7 , 8 ], and biopolymers [ 9 ]. Compared with those, fossil-based to bio-based material production represents a more significant challenge in biosynthesis technology and high-volume output [ 1 ].…”
Section: Introductionmentioning
confidence: 99%